First-class – biosynthesis of 6-MSA and bostrycoidin type I polyketides in Yarrowia lipolytica - Bejenari, Mihaela; Spedtsberg, Eva Mie Lang; Mathiesen, Julie; Jeppesen, Alexandra Claire; Cernat, Lucia; Toussaint, Aouregane; Apostol, Cristina; Stoianov, Victor; Pedersen, Tobias Bruun; Nielsen, Mikkel Rank; Sørensen, Jens Laurids (Frontiers in Fungal Biology, 2024)
Fungal polyketides are a large group of secondary metabolites, valuable due to their diverse spectrum of pharmacological activities. Polyketide production in fungi is associated with several challenges: small yield and low-purity titers. To tackle these aspects, we switched from fungi to the yeast Yarrowia lipolytica, an easily cultivable heterologous host.As an oleaginous yeast, Y. lipolytica displays a high flux of acetyl-and malonyl-CoA precursors used in fatty acid biosynthesis. Likewise, acetyl-and malonyl-CoA are the building blocks of fungal polyketides, and we explored the possibility of redirecting this flux towards polyketide production. Despite its promising prospect, Y. lipolytica has so far only been used for heterologous expression of simple type III polyketide synthases (PKSs) from plants. Therefore, we decided to examine the potential for more complex polyketide production in Y. lipolytica by targeting fungal polyketides derived from type I PKSs. We employed a CRISPR-Cas9-mediated genome editing method to achieve markerless gene integration in Y. lipolytica of the fsr1, fsr2, and fsr3 genes, responsible for bostrycoidin biosynthesis in Fusarium solani and 6MSA gene responsible for 6-methylsalicylic acid (6-MSA) biosynthesis in Aspergillus hancockii. Additionally, we integrated a fourth gene encoding the activating co-enzyme phosphopantetheinyl transferase, FsPPT1, found in F. solani. Moreover, we attempted titer optimization through metabolic engineering by overexpressing two enzymes, TGL4 and AOX2, directly or indirectly involved in the lipid β-oxidation. Still, we did not observe an effect on titers produced by the overexpression strains. Lastly, we also evaluated the effect of growth conditions on the production of the polyketides by cultivating the strains in flat bottom and baffled bottom shake flasks, with the increased aeration generated by the baffled bottom shake flasks leading to a more prolific growth of Y. lipolytica.We achieved titers of up to 403 mg/L 6-MSA and 35 mg/L bostrycoidin, the latter being substantially higher than the yields we previously obtained in Saccharomyces cerevisiae (2.2 mg/L). This work demonstrates the potential of Y. lipolytica as a platform for heterologous production of complex fungal polyketides.